2007
DOI: 10.1111/j.1743-7563.2007.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of esophageal carcinoma following corrosive esophagitis successfully treated with chemoradiation therapy

Abstract: Background: Ingestion of corrosive substances can be associated with severe damage to the esophagus, resulting in strictures. It is also known to be associated with an increased incidence of esophageal carcinoma. In many such cases surgery to cure the cancer is compromised by earlier surgery for corrosive damage or due to fibrosis. Methods: We reviewed a database of 1246 patients collected between 1988 and 2006 with esophageal cancer. Squamous cell carcinomas arising in two patients with previous corrosive eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This result enforced the safety of repeated endoscopic dilatation in our study; no statistical significance was found between the pathological criteria ( i.e ., chronic irritation, reactive epithelial atypia, or low-grade dysplasia) of the oesophageal mucosal biopsies in the three groups and duration of endoscopic dilatation of more than two years. There is a long latency period (12-41 years) between ingestion of caustics and the development of malignancy[6,19,20]. Jain et al[20] reported the first case from India of a 14-year-old boy with an associated 1-year history of accidental caustic ingestion who developed ESCC along with cervical lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This result enforced the safety of repeated endoscopic dilatation in our study; no statistical significance was found between the pathological criteria ( i.e ., chronic irritation, reactive epithelial atypia, or low-grade dysplasia) of the oesophageal mucosal biopsies in the three groups and duration of endoscopic dilatation of more than two years. There is a long latency period (12-41 years) between ingestion of caustics and the development of malignancy[6,19,20]. Jain et al[20] reported the first case from India of a 14-year-old boy with an associated 1-year history of accidental caustic ingestion who developed ESCC along with cervical lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Nozoe et al, out of 259 subjects only 0.8% of the patients with ESCC were younger than 40 years [6]. After searching the literature extensively, there appears to be only a few cases of esophageal carcinoma in children reported so far [1,12,13]. However, there are no case reports on esophageal squamous cell carcinoma due to caustic ingestion in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The only possible etiological factor linked to esophageal carcinoma has been the documentation of the carcinoma developing from lye ingestion [12]. There is however, a long latency period (12-41 years) between ingestion of lye and development of malignancy [4,[12][13][14]. The risk of esophageal cancer in a patient who suffered significant injury after caustic ingestion is reportedly 1,000-10,000 times higher than in normal individuals and is equal in males and females as opposed to the more usual esophageal cancer that is more prevalent in males [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation